2019
DOI: 10.1002/chem.201805260
|View full text |Cite
|
Sign up to set email alerts
|

Octacarbonyl Anion Complexes of the Late Lanthanides Ln(CO)8 (Ln=Tm, Yb, Lu) and the 32‐Electron Rule

Abstract: The lanthanide octacarbonyl anion complexes Ln(CO) 8 À (Ln = Tm, Yb, Lu) were produced in the gas phase and detected by mass-selected infrared photodissociation spectroscopy in the carbonyl stretching-frequency region. By comparison of the experimental CO-stretching frequencies with calculated data, which are strongly redshifted with respectt of ree CO, the Yb(CO) 8 À and Lu(CO) 8 À complexes were determined to possess octahedral (O h ) symmetry and ad oublet X 2 A 2u (Yb) and singlet X 1 A 1g (Lu) electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 56 publications
(33 reference statements)
2
47
0
Order By: Relevance
“…This becomeso bviousf rom the visual inspection of the deformationd ensities and the associated fragment orbital, which are shown below.T he contribution of the uranium 5f AOs to the UÀCO bonds in [U(CO) 8 ] q is much higher than that of the 4f AOs of the lanthanide atoms in [Ln(CO) 8 ] À (Ln = Tm, Yb, Lu), which amount to < 4% of the LnÀCO bondingo rbitals. [10] The EDA-NOCV resultso fT able 3s uggest that the contribution of the uranium valence orbitals possess the trend 6d @ 5f> 7s % 7p. We want to point out that the DE orb values do not only come from genuine orbital interactions between the fragments, they also include intrafragmentp olarization.A previouss tudy of transition metal hexacarbonyls [TM(CO) 6 ] q (TM q = Hf 2À ,T a À ,W ,R e + ,O s 2 + ,I r 3 + )s howedt hat the contribution by polarization is rather small.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…This becomeso bviousf rom the visual inspection of the deformationd ensities and the associated fragment orbital, which are shown below.T he contribution of the uranium 5f AOs to the UÀCO bonds in [U(CO) 8 ] q is much higher than that of the 4f AOs of the lanthanide atoms in [Ln(CO) 8 ] À (Ln = Tm, Yb, Lu), which amount to < 4% of the LnÀCO bondingo rbitals. [10] The EDA-NOCV resultso fT able 3s uggest that the contribution of the uranium valence orbitals possess the trend 6d @ 5f> 7s % 7p. We want to point out that the DE orb values do not only come from genuine orbital interactions between the fragments, they also include intrafragmentp olarization.A previouss tudy of transition metal hexacarbonyls [TM(CO) 6 ] q (TM q = Hf 2À ,T a À ,W ,R e + ,O s 2 + ,I r 3 + )s howedt hat the contribution by polarization is rather small.…”
Section: Resultsmentioning
confidence: 92%
“…The EDA-NOCV methodi sw ell suited for this, because it uses the electronic structure of the molecules for an unbiased analysiso ft he pairwise orbitali nteractions without referring to ar eference system.This has been found very useful in our previous studies of metal octacarbonyl complexes of main-group atoms, [17] transition metals, [16] and late-lanthanide elements. [10] Af ocus of the present work lies on the contribution of the 5f orbitals of the metals to the metal-COb onds. Our previous bonding analysis of the lanthanide octacarbonyl anions [Ln(CO) 8 ] À (Ln = Tm, Yb, Lu) showed that the 4f orbitals of the Ln atoms provide < 4% of the total orbital interactions of the Ln À ÀCO bonds.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations